Immunohistochemical Localization of Epidermal Growth Factor Receptor in Rat Buccal Mucosa Treated with Fenugreek Leaf Oil - A Omran, Sarah; A Ghani ‎, Ban (The Iraqi Journal of Veterinary Medicine, 2024)
The lack of effective treatment for oral mucosal ulcers has motivated clinicians to search for other therapeutic techniques to improve oral ulcer healing. Applying fenugreek to an ulcer triggers the release of its anti-inflammatory components, that might reduce any superfluous inflammatory processes and accelerate wound healing. The aim of this study was to investigate the effect of fenugreek leaf oil on the ulcer associated with the expression of epidermal growth factor receptor (EGFR). A total of 24 adult male rats weighing between 350 and 450 grams and 4-6 months of age were used in this study. The experimental design included: the normal group (no ulcer), the control group (12 ulcers left without treatment to the right), and the study group (12 ulcers on the left side were healed using fenugreek oil). All rats were sacrificed on the 3rd and 7th days of the experimental study, healing durations, and biological samples were prepared for histological and immunohistochemistry analysis of EGFR. The current study exhibited that the EGFR expression increased in ulcer sites treated with fenugreek after 3 days of ulceration with significant differences in comparison with other groups. In conclusion, fenugreek oil was efficient in promoting ulcer healing by enhancing epithelization. Moreover, the positive localization of EGFR increased in the study groups treated with fenugreek oil indicating its potential activity in accelerating the healing process‎‎‎.